PERAN ORANGTUA DALAM MENUMBUHKAN MOTIVASI BELAJAR ANAK - Wahidin (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2018)
This paper discusses the role of parents in improving children’slearning motivation. The children referred to in this paper are children ofprimary school age (SD / MI) ie those aged 6.0 years to 12 years. Parents have avery important role in the education of their children among them as a motivator.In this case the parents should always give encouragement to their children tohave a passion in learning, especially in home study as a supporter of successfulachievement in school. The efforts that can be done by parents in improvingmotivation to learn children include: 1) Knowing the results, 2) Providingrewards and punishments, 3) Provide the necessary tools or facilities. Parentsas educators should always pay attention to the child’s personal developmentas a determinant in the treatment of education in accordance with the period orlevel of age and ability to think child.